(untitled) (American Journal of Islam and Society, 1998)
Globalization is a subject about which it is very easy to write copiously and badly. This is inevitable, given its literal implication of change in everything humanity holds dear, thereby eluding encapsulation within any single paradigm, theory, or perspective. Legions of authors, however, not deterred by this fact have elaborated on their uniquely true reading of the outcomes of this phenomenon, so many carefully avoiding serious criticism of the idea in so doing. Now, as the millenium nears, whole populations are certain in their knowledge that globalization is here, but very few individuals can claim credibly to know what it is, how it works, and where it will take us. One useful approach to doing justice to so broad a topic within a single volume is to engage the services of several authors, each dealing with those facets of globalization for which they are best equipped. This is the approach taken in the work under review, where the talents of 23 individuals have been pooled. The downside is the risk that no tangible concept of globalization will emerge from the various contributions and that the reader will be left unconvinced that so many disparate treatments describe the same subject. Editors Kofman and Youngs exhibit some sensitivity to this problem and, to their credit, designed their book to encompass a sizable part of the intellectual territory of globalization. From the vantage points of geography, politics, and international relations, as well as sociology, law, and even epistemology, each author shares his or her view of globalization in action. If, at times, the view is from quite a distance or obstructed by foreground issues of only indirect importance, this is compensated for by the novelty of the perspectives offered. As far as intellectual coverage is concerned, a stronger economic content is notable by its absence, for although economists have their say on the subject nearly everywhere else, the intimacy between politics and economics (as opposed to capitalism) in the context of globalization deserves every attention. Kofman and Youngs are anxious to position this work as part of the “second wave” of serious and scholarly research on globalization, although in so doing they tend to assume that the “first wave” (presumably consisting of descriptive or historical narratives) yielded a solid enough foundation on which to build. The fact remains that the very hypothesis of globalization has its detractors, and in their introduction, the editors fail to convince the critical reader of globalization’s conceptual or empirical validity. Similarly, several later chapters could easily be rewritten without recourse to “the G word,” for they are more useful as perspectives on postlmodernism, capitalism, interhationalism, internationalization, or regionalism, to name only a representative selection. Although many participants in academic discourse comprehend globalization in its particular manifestations, others, myself included, prefer that its elaboration on a holistic level should be featured just as often. The tendency to work within the “globalization of ...” framework, rather than “globalization is ...,” eventually may obscure vital truths of the same variety as a failure to see the forest shrinking due to focused interest in the growth of individual trees. A book such as this should, by its close, clarify what globalization is not, in order to demonstrate the theory’s tractability. This would serve the additional purpose of countering those who write globalization off as fantasy, or worse, as a conspiracy to revive the fortunes of authors exhausted on other intellectual fronts. Unfortunately, despite its ostensible commitment to the “is” approach, a good deal of Globalizution is intent on describing the more readily circumscribed incidents of an ineffable force ...